2016
DOI: 10.1590/2317-1545v38n1155449
|View full text |Cite
|
Sign up to set email alerts
|

Physiological changes in Jatropha curcas L. seeds during storage

Abstract: -Oil seeds, such as J. curcas, are more prone to deterioration and consequently to loss of quality during storage. In this context, adequate technics for its preservation are of great importance. This study aimed to evaluate the effects of different environments and packaging for the conservation of J. curcas seeds during twelve months of storage. The seeds were placed in three different types of packaging: a multiwall paper bag (or Kraft paper bag); a cloth bag; and a high-density plastic bag. After this, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 11 publications
1
6
0
1
Order By: Relevance
“…This damage might have contributed to lixiviation of the solubles, which are essential for the preservation of the quality of the produce and, consequently, its storability. With the deterioration of cellular integrity, lixiviation of solubles occurs because the cellular membranes no longer efficiently function as a selective barrier at the start of absorption, and thus resulted in higher electrical conductivity values in the solution (Dias et al, 2016;Hartmann Filho et al, 2016). Deterioration often occurs when the product is stored under extreme conditions, such as storage for long periods at high temperatures because membrane integrity is gradually deteriored (Bezerra et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This damage might have contributed to lixiviation of the solubles, which are essential for the preservation of the quality of the produce and, consequently, its storability. With the deterioration of cellular integrity, lixiviation of solubles occurs because the cellular membranes no longer efficiently function as a selective barrier at the start of absorption, and thus resulted in higher electrical conductivity values in the solution (Dias et al, 2016;Hartmann Filho et al, 2016). Deterioration often occurs when the product is stored under extreme conditions, such as storage for long periods at high temperatures because membrane integrity is gradually deteriored (Bezerra et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…With respect to storage practices, storage temperature and storage period, which are the most important variables; storage temperature can affect product quality during the storage period, while the storage period can accentuate product deterioration (Zonta et al, 2014;Polat, 2015;Dias et al, 2016). In this context, product deterioration involves dry matter losses, changes in color, and poor quality of by-products such as crude oil, due, mainly, to the lipidic deterioration, wich have the ability to elevate some undesirable characteristics undesirable to the oil, like the acidity and peroxide content (Del Campo et al 2014;Paraginski et al 2015;Hartmann Filho et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Marcos Filho [7] recommends that oil seeds should be stored with a moisture content lower than that indicated for amylaceous, between 8% and 10% [21]. Dias et al [22] evaluating different environments and conservation packaging of jatropha seeds during 12 months of storage analyzed that there was a reduction in the physiological quality of the seeds kept in a laboratory environment independent of the packaging used and that the most adequate condition for storage of seeds should be in a plastic bag in a cold room (10˚C ± 2˚C, 55% ± 5% RH) that is with a low RH%.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, different researches showed that the GP of J. curcas changed according to provenance, for example, between 50% to 89% in seeds from Africa [56], 98.96% in hybrid from Malaysia and Indonesia and 53.43% in hybrid form Cape Verde and South Africa [19]. Also, the germination percentage can varies according to the substrate used for germination test [57], being superior in sand than in clay [58]. In addition, it was observed that the GP change from 74% to 88% in fruits with different ripening state [58].…”
Section: Seed Viability Test After Aging Treatmentmentioning
confidence: 99%